2017
DOI: 10.1186/s40795-017-0159-x
|View full text |Cite
|
Sign up to set email alerts
|

Foods tabooed for pregnant women in Abala district of Afar region, Ethiopia: an inductive qualitative study

Abstract: Background: Food taboo is contributing substantially to malnutrition for pregnant women by restricting and limiting the frequency and variety of foods most of which are nutritious and easily accessible. The practice is common in developing countries and most of the food taboos in East Africa fall on the women and most unfortunately on the pregnant. Foods of animal products, which are the main sources dietary energy of pastoralist communities, are often prone to the practice of food taboos. Nonetheless, the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 18 publications
4
36
0
Order By: Relevance
“…Most of the foods that were reported as taboo are rich sources of essential micronutrients, which are crucial for maternal health and child growth and development. Findings from the current study support others in which food taboos during pregnancy were found to be more elaborate, nutritionally significant, and differ only in the type and reasons attached to avoidance of the food type [ 4 , 5 , 15 17 ].…”
Section: Discussionsupporting
confidence: 86%
“…Most of the foods that were reported as taboo are rich sources of essential micronutrients, which are crucial for maternal health and child growth and development. Findings from the current study support others in which food taboos during pregnancy were found to be more elaborate, nutritionally significant, and differ only in the type and reasons attached to avoidance of the food type [ 4 , 5 , 15 17 ].…”
Section: Discussionsupporting
confidence: 86%
“…Most of the foods that were reported as taboo are rich sources of essential micronutrients, which are crucial for maternal health and child growth and development. Findings from the current study support others in which food taboos during pregnancy were found to be more elaborate, nutritionally signi cant and differ only in the type and reasons attached to avoidance of the food type (4)(5)(6)16,17).…”
Section: Discussionsupporting
confidence: 86%
“…Restrictive dietary behaviour was positively associated with anaemia in Somali region where women are expected to reduce the size and frequency of meal during pregnancy (Kedir, Berhane, & Worku, 2013). Also, a study in Afar region revealed that eating large amount of any food, meat and solid food are tabooed for pregnant women which may result them to malnutrition (Hadush, Birhanu, Chaka, & Gebreyesus, 2017). The lowest utilization of maternal health services in Afar and Somali (Bobo et al, 2017) and recurrent drought‐triggered food insecurity might have contributed for the higher prevalence of anaemia in these regions (FMOH, 2008).…”
Section: Discussionmentioning
confidence: 99%